Femoral hernia in the era of TAVI – a potential obstacle for transfemoral approach: a case report and literature review - Piotr Marciniuk; Dariusz Jagielak; Jan Rogowski; Piotr Gumiela; Kamil Bury (BMC Surgery, 2020)
Abstract Background Transcatheter aortic valve implantation (TAVI) via total percutaneous transfemoral approach is an increasingly common technique for aortic stenosis treatment. It is primarily indicated in elderly with serious comorbidities. The epidemiology of these patients tends to overlap with the incidence of femoral hernia (FH). The appearance of hernia sac at the approach site and insufficient preoperational examination can lead to serious complications. We present the first-ever reported case of subsequent femoral hernia repair during transfemoral TAVI. Case presentation This report presents a case of FH/TAVI coincidence and literature review of its epidemiology. Literature review was performed to analyze similarities of femoral hernia and TAVI. The case describes an 84-year old female referred for elective TAVI. Intraoperation incarcerated femoral hernia was noticed and directly repaired. Further TAVI steps were performed on regular basis. A 2-year follow-up reported no local and general complications related to procedures. Conclusions Unsuspected femoral hernia found subsequently with transfemoral TAVI may become a growing problem. The number of TAVI performed rises with indications expansion. Femoral hernia repairs constitute from 2 to 4% of all groin hernia. Both TAVI and FH are connected with elderly. Despite the fact of low FH incidence, growing number of TAVI performed and ageing of population, corresponds with higher possibility of complications. Most of these complications may end up fatal as they would involve high-risk patients. Insufficient attention is paid by cardiologists to the possible hernia appearance in the access site as this issue has been hardly ever presented in literature. Concomitant FH in TAVI patients should always be excluded in order to avoid serious complications. The case we report presents a successful subsequent FH repair during TAVI procedure. Further studies have to be conducted to provide data on how such problems ought to be managed.